Comparative advantages in Polish export to the European Union — food products vs selected groups of non-food products - Iwona Szczepaniak (Oeconomia Copernicana, 2018)
Research background: Globalisation and economic integration are the reasons for which the competitiveness of economic entities is analysed more and more often in the context of their relations with the international market. One of the ways to assess the competitiveness of the Polish food sector is an analysis of comparative (relative) advantages in the export of this sector’s products.